MEDIASI NON-LITIGASI: MENCAPAI KESEPAKATAN DAMAI DALAM KONFLIK SYIQAQ DAN NUSYUZ UNTUK KEHARMONISAN KELUARGA PERSPEKTIF HUKUM KELUARGA ISLAM - Saini, Saini (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
For family problems, people are more likely to use non-litigation mediation processes to resolve their disputes rather than litigation. This is caused by many factors, including high costs, a long process, community obedience to kiai and community leaders, and long distances. The aim of this research is to find out how effective village kiai are as non-litigation mediators in resolving syiqaq and nusyuz conflicts and how Islamic law reviews village kiai's non-litigation mediation practices in resolving family problems. This study conducted descriptive qualitative research. The results show that the village kiai was chosen as a non-litigation mediator based on community beliefs. In practice, he provides direction and helps close deals. Furthermore, the principles of Islamic law state that it does not conflict with Islamic law, and even qualifies as a hakam.